2020
DOI: 10.1111/jocn.15444
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study of mental health status and self‐psychological adjustment in nurses who supported Wuhan for fighting against the COVID‐19

Abstract: Aims and objectives: To evaluate the mental health status, stressors and self-adjustment of nurses in isolation wards at different periods in Wuhan, China. Background: Mental health issues easily occurred among the frontline medical workers of a major epidemic. However, the stressors and psychological adjustments experienced by nurses have not been well described. This is crucial to improving clinical quality and nursing safety and ensuring nurses' physical and psychological health. Methods: We performed a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
1
39

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(118 citation statements)
references
References 34 publications
(36 reference statements)
11
67
1
39
Order By: Relevance
“…Studies from China have found that the frontline healthcare personnel, especially the nursing staff, caring for patients with COVID-19 are at risk of anxiety and mental health problems [4,32]. Similar results have been described in studies from Germany [8], Israel [33], Portugal [34], and Turkey [35].…”
Section: Discussionsupporting
confidence: 71%
“…Studies from China have found that the frontline healthcare personnel, especially the nursing staff, caring for patients with COVID-19 are at risk of anxiety and mental health problems [4,32]. Similar results have been described in studies from Germany [8], Israel [33], Portugal [34], and Turkey [35].…”
Section: Discussionsupporting
confidence: 71%
“…24 Nurses were worried about being infected while delivering care. 25 Additionally, most of them had not participated in public health emergency rescue before, had little coping experience and were not well prepared for frontline work. 26 Receiving psychological intervention or training before or during the frontline work period might have helped nurses maintain positive affect and reduce their attention bias to 27 thus helping them complete highintensity work in a good psychological state.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies identified specific coping mechanisms employed by HCWs during the pandemic (Blanco-Donoso et al ., 2020; Cai, 2020; Chen et al ., 2020; Chew et al ., 2020; Dong et al ., 2020; Giusti et al ., 2020; Labrague & De los Santos, 2020; Maraqa et al ., 2020; Mi et al ., 2020; Nie et al., 2020; Salman et al, 2020; Shechter et al ., 2020; Vagni et al ., 2020; Xiao et al ., 2020). During the pandemic, HCWs utilized both negative and positive coping styles to manage stress.…”
Section: Methodsmentioning
confidence: 99%